The Effect Of Picture Series Teaching Media To The Writing Ability Of Grade Eighth Students Of SMP Negeri 9 Pematang Siantar On Narrative Text - Joint Tondang; Sanggam Siahaan; Novra Melisa P. Hutabarat (CV Putra Publisher, 2023)
The goal of this research is to find out the effect of picture series teaching media to the writing ability of grade eighth students of SMP Negeri 9 Pematang Siantar on narrative text. This research was using a quasi-experimental design to find out this research. The sample of the research were taken from two classes that consist of 58 students, 29 students in experimental class at VIII-8 and 29 in control class at VIII-7. The resercher found the total of mean score of pre-test in experimental class is 56,53 while mean in post-test is 71,2. The mean score of pre-test in control class is 50,79 while mean in post-test is 60,7. After calculated the data from all of the score, the researcher found that t-test score is 4,06. The, the researcher calculated with score on t-table uses significance 0.05 and the value is 1.672. So, the researcher found that t-test is higher than t-table (4.06 > 1.672). It can be conclude that the effect of picture series teaching media to the writing abilty of grade eighth students of SMP Negeri 9 Pematang Siantar on narrative text.